2011
DOI: 10.1111/j.1468-1331.2011.03355.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine gene polymorphisms in multiple sclerosis: a meta-analysis of 45 studies including 7379 cases and 8131 controls

Abstract: Many environmental and genetic factors have been implicated in the development of multiple sclerosis. However, the aetiology has not been clarified yet. Therefore, using a meta-analytic approach, we tried to probe the potential association between various cytokine gene polymorphisms and the occurrence of multiple sclerosis. A comprehensive literature search yielded 45 eligible studies, which involved 7379 cases and 8131 controls. Totally, the effect of eight polymorphisms, i.e. IL-1A C[-889]T, IL-1B C[-511]T, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 97 publications
1
5
0
Order By: Relevance
“…Similar to our study, Nikolopoulos et al [37] performed a meta-analysis of the IL10 -1082 and IL10 -819 SNPs in MS. In a recessive model, the GG genotype (IL10 -1082 SNP) was associated with MS.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Similar to our study, Nikolopoulos et al [37] performed a meta-analysis of the IL10 -1082 and IL10 -819 SNPs in MS. In a recessive model, the GG genotype (IL10 -1082 SNP) was associated with MS.…”
Section: Discussionsupporting
confidence: 73%
“…Six case-control studies [24,25,27,[29][30][31] and one cohort article [34] were identified for the IL10 -819 SNP, and five case-control studies [24,27,29,30,33] and one cohort [34] studies addressed the IL10 -592 SNP. We also included one review [36] and two meta-analyses [37,38] among the selected articles (Table 1).…”
Section: Selection and Characteristics Of Included Studiesmentioning
confidence: 99%
“…It is made available under The copyright holder for this preprint (which was not this version posted January 29, 2018. ; https://doi.org/10.1101/236158 doi: bioRxiv preprint Accordingly, suicide has been found to occur up to 3 times more in MS patients than in the general population, becoming one of the leading causes of death in this particular group [26]. Also, interleukins 1a, 1b, and 6, TNF-alfa, or C-reactive protein have been widely described elevated in MS patients [27] as in patients with psychiatric manifestations mainly expressing psychosomatic symptoms [28], [29]. At this time, we were unable to measure inflammation biomarkers, but we believe that the difference found between RR and SP could be related to the inflammation process of MS, where RR-MS patients have been found…”
Section: Discussionmentioning
confidence: 99%
“…Also, interleukins 1a, 1b, and 6, TNF-alfa, or C-reactive protein have been widely described elevated in MS patients [28] as in patients with psychiatric manifestations mainly expressing psychosomatic symptoms [29], [30]. At this time, we were unable to measure inflammation biomarkers, but we believe that the difference found between RR and SP could be related to the inflammation process of MS, where RR-MS patients have been found to have a more acute inflammation response than SP-MS patients.…”
Section: Discussionmentioning
confidence: 99%